PENJADWALAN BATCH PADA SISTEM PRODUKSI JOB SHOP SINGLE ITEM MULTI - Asih, Endang Widuri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2004)
Peripatetic company in area manufacture will not get out of the that company ability to run its operation. Environmental problems optimation of manufacture usually hit the finite resource allocation of its amount in a few work area. With the certain criterion performance, the problems optimation is usually finished. One of form optimalitation in system manufacture is by scheduling existing production facility to finish some job. Two general criterion which often weared to evaluate the performance scheduling is makespan and flow time. At this research is conducted to compare the minimum makespan is by using overlapping method and without using overlapping method. Overlapping method is division of a number of part to be produced by multi stage into some batch in such a way that the batch can be parallelly processed. Batch scheduling by using overlapping method represent the optimal solution by minimation makespan. Total the optimal batch as much 2. Makespan got is equal to 148745,08 minute, smaller than makespan got without using overlapping method that is equal to 152000 minute. Big of time thrift is equal to 2,14%.